Implementation of the Early Warning Application Program for Pregnant Women to Support Health Services in Rural Areas - Kamisutara, Made; Muchayan, Achmad; Artaya, I Putu; IGA. Sri Deviyanti (PT Mattawang Mediatama Solution, 2023)
The development process of digital technology has affected many fields. One of them is health field. Number of health application appears. They can be accessed easily by smartphone or tablet device. For instance, in developed countries, doctors examine and diagnose children's ears using smartphone. He provides the appropriate treatment for their patients through the device. The growing number of mobile applications in health will certainly facilitate patient care. There are currently about 13,000 digital health applications. Nowadays, patients have gradually followed this trend. Rock Health, as a provider of digital health ecosystem services, explains the power of mobile health care as well as the health effects of technology. The digital health care industry has a significant impact on healthcare providers. In this research, the researchers design tools or web-based applications and or sms gate way. The main objective is to monitor early health for expectant mothers and infants who are less likely to receive direct medical care.